Alex - 1951-; Wynne, Frank (New York : MacLehose Press, 2013)
In kidnapping cases, the first few hours are crucial. After that, the chances of being found alive go from slim to nearly none. Alex Prevost, beautiful, resourceful, tough, may be no ordinary victim, but her time is running out. Commandant Camille Verhoeven and his detectives have nothing to go on: no suspect, no lead, rapidly diminishing hope. All they know is that a girl was snatched off the streets of Paris and bundled into a white van. The enigma that is the fate of Alex will keep Veroeven guessing until the bitter, bitter end. And before long, saving her life will be the least of his worries. --from publisher.
Lariat Reading List, TLA 2014
Keywords: Kidnapping -- Fiction; Suspense fiction